2011
DOI: 10.1021/jf201496h
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Dietary Fish-Oil-Derived Monounsaturated Fatty Acids on Metabolic Syndrome Risk Factors and Insulin Resistance in Mice

Abstract: The aim of this study was to elucidate the effect of fish-oil-derived monounsaturated fatty acids (MUFAs) containing large amounts of C20:1 and C22:1 isomers on metabolic disorders in mice. Male C57BL/6J mice were fed a 32% lard diet (control) or a 27% lard plus 5% saury-oil-derived MUFA diet for 6 weeks. Dietary MUFA improved insulin resistance and alleviated metabolic syndrome risk factors by reducing blood glucose and lipids. These favorable changes may be attributed to an improved adipocytokine profile. MU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 37 publications
2
59
0
Order By: Relevance
“…For example, supplementation of eicosapentaenoate and DHA protects mice from HF-induced body weight gain, dyslipidemia, and glucose intolerance (23). Dietary supplementation with monounsaturated FAs improves insulin sensitivity and adipokine and lipid profiles in the HF-fed mice and healthy young subjects (44,47). Although no evidence directly addresses the relationship between dietary unsaturated FAs and in vivo mitochondrial morphology, our results, together with those of other studies, suggest that supplementation with unsaturated FAs can reverse insulin resistance and in vivo mitochondrial morphology defects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, supplementation of eicosapentaenoate and DHA protects mice from HF-induced body weight gain, dyslipidemia, and glucose intolerance (23). Dietary supplementation with monounsaturated FAs improves insulin sensitivity and adipokine and lipid profiles in the HF-fed mice and healthy young subjects (44,47). Although no evidence directly addresses the relationship between dietary unsaturated FAs and in vivo mitochondrial morphology, our results, together with those of other studies, suggest that supplementation with unsaturated FAs can reverse insulin resistance and in vivo mitochondrial morphology defects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yang and others examined the effect of LC-MUFA-concentrated oil on metabolic disorders and found that consumption of LC-MUFA at a dose of 4-7 w/w improves several metabolic parameters in obese and type 2 diabetic mice 45,46 . Based on these results, there is a possibility that eicosenoic acid plays a role in the positive effect of SO on lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Blood ketone levels remain unchanged after supplementation with fish-oil [42]. Fish-oil supplemented and derived diets in mice reduce total plasma cholesterol and either decrease or have no effect on plasma triglyceride levels [43-45]. Fasting glucose in mice remains unchanged or is decreased in mice given fish-oil supplemented or derived diets [44-46].…”
Section: Introductionmentioning
confidence: 99%